Revisiting transdominant-negative proteins in HIV gene therapy. (August 2013) - Sivakumaran, Haran; Cutillas, Vincent; Harrich, David
HIV remains a global public health issue and new therapies are actively being developed. Traditional treatments such as small-molecule inhibitors are being investigated; however, newer modalities are also being pursued, including the use of transdominant-negative proteins. A transdominant negative is a mutant of a protein designed to interfere with the normal activity of its wild-type counterpart. Transdominant negatives designed to block HIV replication are based on viral proteins; however, recent approaches show that transdominant negatives of cellular proteins have therapeutic potential. Recent discoveries have revealed that treatments based on transdominant negatives can greatly disrupt the replication cycle of the virus. This article aims to review viral and cellular protein-based transdominant negatives, the recent elucidation of their modes of action and their potential use in HIV gene therapy.